PROSPECTS AND OPPORTUNITIES FOR THE DEVELOPMENT OF HALAL TOURISM IN THE ISSYK-KUL REGION - Abytaeva U. T.; Mambeteminova Ch. B.; Turdukeeva M. (Vestnik Issyk-Kulʹskogo universiteta, 2025)
This abstract provides a brief overview of the prospects and potential of organizing halal tourism in the Issyk-Kul region. The possibilities of organizing halal tourism in the Issyk-Kul region are considered. The history of the formation of Islam in the territory of modern Kyrgyzstan is considered. The concept of halal tourism and the relationship of religion with tourism are defined. The prospects and problems of developing halal tourism in the region are analyzed. The advantages and opportunities of halal tourism in the Issyk-Kul region are studied. The existing potential for the development of halal tourism, the existing attractions of the city of Karakol are listed. Approaches to the development of halal tourism include the creation of infrastructure that meets the requirements of the halal lifestyle, offering cultural and religious attractions, as well as providing quality services and hospitality. Development paths aimed at meeting the needs of halal tourists and the sustainable development of the tourism industry in the region are also proposed. These tourists may be interested in visiting places that offer halal services and products, such as mosques, halal restaurants and hotels, as well as excursions and entertainment that do not conflict with their religious beliefs.